(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
The impact of human development on this planet has been huge and often damaging. The discipline of medical bioethics addresses these and other ethical issues involving health care professionals and healthcare seekers. Bioethics thus forms the interface between medicine, law, biotechnology, health policy and philosophy. The UNESCO bioethics curriculum encompasses several principles namely-Human dignity and right, benefit and harm and individual responsibility. The UNESCO adopted the bioethics curriculum so that student learn to identify ethical issues in medicine, health care and life sciences and apply the ethical principle of universal declaration on bioethics and human rights on situation. The Department of Psychiatry at PGIMER-RML hospital was the natural choice for establishing the central India unit of the UNESCO chair at Haifa. Given the awareness of human rights the growing bioethics movement in country will help restore relationship of care and respect among patients. Let us raise hands on issues which are important to us.